Spatial Hierarchy In The Tengger House, Ranu Pani Village - Sani Syauqi Azmi; Lisa Dwi Wulandari; Yusfan Adeputera Yusran (Department of Architecture Universitas Muhammadiyah Jakarta, 2022)
The Tengger tribe inhabits the Bromo Tengger Semeru National Park area, a national park area that is synonymous with natural and cultural tourism. Among the villages in the Tengger area, Ranu Pani Village is the most recently administratively formed village in 2001. The uniqueness of Ranu Pani Village is located in the middle of the National Park area so that its status as an enclave village. With this status, the village cannot increase its land expansion because it is confined to a protected forest area. it is common for Ranu Pani houses are often found between children and parents close together. The existence of residential houses that are close to those of parents and children as well as tourists make the space users of a house diverse. The privacy of a space is interesting to know from the space in the house in Ranu Pani Village which has different dynamics of function and occupants of the space. method used in this study is a descriptive qualitative method. The results of the study show that the basic hierarchy of spatial from houses in Ranu Pani Village still has many similarities with other Tengger studies, but some have adapted with form and function from the house.